Prisons in pandemic time: a different way to survive coronavirus - Goicochea Elías, José Julio (2020)
The pandemic situation that the planet is going through has overwhelmed all the health facilities and programs. The penitentiary detention centers have not been oblivious to this reality. To the known problems of an infrastructure overwhelmed by the inmate population and to the scarce medical attention that a high percentage of infectious-contagious diseases brings, this new virus is added, the full effects of which are unknown. It is also worrying that a high number of the prison population is still facing sentencing processes: due to excessive abuse of the preventive detention mechanism and the almost null application by the judicial operators of the principles of proportionality and reasonableness. Jail is the exception. The judges have made it the rule.